Development and validation of the activity significance personal evaluation (ASPEn) scale. (4th October 2014) - Mallinson, Trudy; Schepens Niemiec, Stacey L.; Carlson, Mike; Leland, Natalie; Vigen, Cheryl; Blanchard, Jeanine; Clark, Florence
<x xml:space="preserve">Abstract</x> Background/aim Engagement in desired occupations can promote health and wellbeing in older adults. Assessments of engagement often measure frequency, amount or importance of specific activities. This study aimed to develop a scale to measure older adults' evaluation of the extent to which their everyday activities are contributing to their health and wellness. Methods Eighteen items, each scored with a seven‐point rating scale, were initially developed by content experts, covering perceptions of how daily activities contribute to physical and mental health, as well as satisfaction and activity participation in the last six months. Rasch analysis methods were used to refine the scale using the pencil and paper responses of 460 community‐living older adults. Results Initial Rasch analysis indicated three unlabelled rating scale categories were seldom used, reducing measurement precision. Five items were conceptually different by misfit statistics and principal component analysis. Subsequently, those items were removed and the number of rating scale steps reduced to 4. The remaining 13‐item, 4‐step scale, termed the Activity Significance Personal Evaluation (ASPEn), formed a unidimensional hierarchy with good fit statistics and targeting. Person separation reliability (2.7) and internal consistency (.91) indicated the tool is appropriate for individual person measurement. Relative validity indicated equivalence between Rasch measures and total raw scores. Conclusions ASPEn is a brief, easily administered assessment of older adults' perception of the contribution of everyday activities to personal health and wellness. ASPEn may facilitate occupational therapy practice by enabling clinicians to assess change in meaning of an older adult's activity over time.